(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The project focused on the Academic Office of Bestlink College of the Philippines-Bulacan Inc. Academic offices are responsible for the maintenance and supervision of institutions. The academic office consists of different modules such as scheduling, loading, observation, monitoring, and immersion. The researchers found out that the school is still using a manual process. The proponents developed an automated system to ease the daily workload inside the academic office. The project team used Agile methodology for this project because of its fast output making. Agile is a methodology for software development that involves the collaborative effort of self-organizing cross-functional teams and their customers. This project started with researching, interviewing, and collecting ideas from the client of the project. Then, the researchers conducted a meeting and made a plan on how to start the project. The scrum master assigned a task for each member for the project plan to be done on the target date that the scrum master has given to the development team. The team made a design and developed the system based on the design process and information gathered from the client and kept in touch with their adviser for advice in creating user stories and do the given task. Afterward, the team ran and tested the system, and it ran successfully. The final step of the project was released. As a result, this project became useful for the academic office. Building lessened the heavy workloads of the dean. Scheduling of classes is now easy because of this new system. It can avoid the redundant recording of schedules that is often the problem of the academic department. Loading can now easily be assigned to teachers based on their available regular load, overload, and mastery of subjects. The observation result of the teachers that are evaluated by the dean can now be saved in the database. With this system, the observation record of a specific teacher can now be easily accessed by searching for it in the system. They can also avoid unexpected damages on paper because the information is now saved in the database. The results of the daily monitoring of teachers can be also saved in the database. The proponents concluded that the system for the academic office is useful in terms of scheduling, monitoring, observation, and generating a report. Project teams recommended having an automated system in the future for fast and easy use of the system and to lessen other manual work.